URGENSI MASLAHAH DALAM KONSEP EKONOMI SYARIAH - Sakirman, Sakirman (IAIN Palopo, 2016)
AbstractThe fragility of the economic system of capitalism and socialism makes the Islamic economicsystem into an alternative economic system and studied in depth by contemporary Islamiceconomic thinkers. In realizing Islamic economic system must be aligned with the maqasid alshariah(goals sharia). There are four main approaches in the study of Islamic economicsnamely: a pragmatic approach, recitative, utopian and adaptive. Such an approach alwaysleads to moral values, human brotherhood, social justice, integrating Islamic values and aimsfor the establishment of al-mashlahah as the core maqashid al-shariah can be used as anargument of the legal establishment, especially relating to Islamic economics. Ijtihad in Islameconomy by using al-maslahah can be done by meeting certain requirements that do notconflict with al-Quran and al-Hadith and not contrary to qiyas. Besides, it does not conflictwith a higher benefit, both in how to do it and in a way to preserve from extinction. EconomicIjtihad Islam implemented by analyzing the social and political realities and priorities (fiqh fighrealities and priorities) in order to achieve the benefit of society and the state.